2015
DOI: 10.1016/j.gfj.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and stakeholder governance around the world

Abstract: In this paper, we examine the impact of stakeholder governance on corporate social responsibility (CSR) around the world to determine whether CSR is employed as a mechanism to mitigate conflicts of interest between managers and diverse stakeholders, or used as managerial perquisites. To examine this relation properly, we not only employ a large and extensive sample of international firms, but also control for endogeneity by using dynamic panel generalized method of moments (GMM), propensity score matching, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 104 publications
1
10
0
1
Order By: Relevance
“…Martínez‐Ferrero et al (2015) argue that in countries with stronger investor protection, companies tend to be shareholder‐value‐oriented. Jo et al (2016) find that the engagement of CSR activities in different countries is found to be affected by country‐level institutions, especially in countries characterized by weak investor protections and weak board governance. El Ghoul et al (2016) find that family firms are less likely to invest in CSR in countries with weaker investor protection.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Martínez‐Ferrero et al (2015) argue that in countries with stronger investor protection, companies tend to be shareholder‐value‐oriented. Jo et al (2016) find that the engagement of CSR activities in different countries is found to be affected by country‐level institutions, especially in countries characterized by weak investor protections and weak board governance. El Ghoul et al (2016) find that family firms are less likely to invest in CSR in countries with weaker investor protection.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…environmental information (Coluccia et al, 2018). Previous studies have shown a positive influence of the rule of law on environmental disclosure (Cahan et al, 2016;Coluccia et al, 2018;Jo et al, 2016). Therefore, the authors hypothesize the following:…”
Section: The Mirror Effectmentioning
confidence: 97%
“…In addition, this indicator measures the quality of contract enforcement, property rights, the police and the courts (Kaufmann et al, 2011). Countries with a better rule of law create a more transparent legal system with regulations for investor protection (Jo et al, 2016). In these countries, investors demand more information from companies, e.g.…”
Section: The Mirror Effectmentioning
confidence: 99%
“…The interaction and relationships between social actors and the firm is however complex. In a context that is dynamic, managers face the challenge of dealing with its stakeholders’ diverse perspectives, interests, and values (Jo et al., 2016) and aligning them to the firm's operations, strategy, and performance expectations. Identifying areas of shared value creation is essential to this process.…”
Section: Introductionmentioning
confidence: 99%